Analisis Penilaian Atas Harga Wajar Saham Menggunakan Metode Discounted Cash Flow (DCF) dan Dividend Discount Model (DDM) Untuk Pengambilan Keputusan Investasi (Studi pada Indeks LQ-45 Periode 2018-2022) - Hutagalung, Jeriko N.J.; Alexandri, Mohammad Benny (Universitas Batanghari, 2024)
This study aims to analyze a stock fundamentally in the LQ-45 Index for the 2018-2022 period using absolute methods, namely the Dividend Discount Model (DDM) and Discounted Cash Flow (DCF) methods so that it can be seen whether the stock condition is undervalued, overvalued, or fairvalued and this will also provide an investment decision recommendation for investors. This type of research is quantitative with a descriptive approach. The main object of research is companies included in the LQ-45 index for the period 2018-2022. This research sampling technique uses purposive sampling so as to produce as many as eight companies in accordance with certain criteria. The results of research using the Dividend Discount Model (DDM) method show that some stocks in undervalued conditions are in ASII, BBNI, BMRI, ICBP, INDF, and TLKM stocks. Then for stocks in overvalued conditions there are ANTM and HMSP shares. In using the Discounted Cash Flow (DCF) method, stocks in undervalued conditions are ANTM, ASII, BMRI, and INDF shares. Then for stocks in overvalued conditions are BBNI, HMSP, ICBP, and TLKM. The results of determining the most accurate method between Discounted Cash Flow (DCF) and Dividend Discount Model (DDM) where the results of measurements using Root Mean Square Error (RMSE) show that the Dividend Discount Model (DDM) method is more accurate in this study.